Addition turmeric extract on ration to reduce fat deposit of broiler. (July 2020) - Utami, M M D; Dwiani, H P; Agus, A.
Abstract: The purpose of this research was to investigate the effect of turmeric extract in ration to reduce fat of broiler. Ninety-day old chicks randomly divided into five treatments: T1 is group received basal diet (control), T2 (0.02% of turmeric extract); T3 (0.04% of turmeric extract); T4 (0.06% of turmeric extract), and T5 (0.08% of turmeric extract). Each treatment consists of three replications and each repetition consist of six chickens. This research using a completely randomized design. The parameters of research were carcass weight, abdominal fat weight and the percentage of abdominal fat. The result of this research showed that turmeric extract had significantly effect (P<0.05) to increase carcass weight (T1: 1476, 7 g; T2: 1503, 8 g; T3: 1577, 0 g; T4: 1633, 7 g; T5: 1605, 0 g), to reduce abdominal fat weight (T1: 34, 33 g; T2: 30, 69 g; T3: 27, 03 g; T4: 26, 96 g; T5: 25, 92 g) and the percentage of abdominal fat (T1: 2, 33%, T2: 2, 04%, T3: 1, 72%, T4: 1, 65%, T5: 1, 63%). The result showed addition turmeric extract on ration increased carcass weight and decreased abdominal fat weight and the percentage of abdominal fat.